Perceptions of High-Risk Situations for Sexual Assault: Gender Differences in the U.S. Air Force. (21st March 2019) - Silber Ashley, Olivia; Lane, Marian E; Morgan, Jessica Kelley; Charm, Samantha; Tharp, Andra; Brown, Mark
Abstract: This study explored U.S. Air Force service members' perceptions of high-risk situations for sexual assault victimization. Qualitative data were collected from 52 active duty Airmen, including sexual assault survivors and general population officers and enlisted personnel. Participants were recruited through posted flyers, base-wide e-mail messages, and referrals from the Sexual Assault Response Coordinator's office. Content analysis was used to summarize participants' opinions and experiences. High-risk situations for all Airmen included excessive alcohol use, specific physical settings, and situations associated with work assignments. High-risk situations identified frequently by male and female sexual assault survivors and female (but not male) general population Airmen included power imbalance; isolation in the workplace and social settings; and youth, inexperience, and unfamiliarity with the military environment. Female Airmen identified workplaces with a predominance of men or being one of very few women in a group as a high-risk situation for sexual assault victimization. And female sexual assault survivors identified implicit but unwarranted trust between Airmen as a high-risk situation. This study provides new insight into gender differences in high-risk situations for sexual assault victimization, and the data can help policymakers better prevent sexual assault by appropriately tailoring and timing sexual assault risk reduction training.